THE EFFECT OF KASTURI (Mangifera Casturi) BARK EXTRACTS AT CONCENTRATION OF 12.7% ON THE NUMBER OF MACROPHAGES AFTER TOOTH EXTRACTION - Nadhira Agnia Rosdayatri; Didit Aspriyanto; Irham Taufiqurrahman (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Tooth extraction is a surgical procedure to take part of the tooth that exposes the bone and soft tissues of the oral cavity. The wound will occur in the soft tissue, and hard tissue around the extraction area after the tooth extraction. Wound healing after tooth extraction begins with the inflammatory phase, in which the movement of leukocytes occurs, such as neutrophil cells. If the wound is chronic, it will be replaced by macrophages. Macrophages are the dominant cells in chronic inflammation and have a role in phagocytizing bacteria and clean damaged tissue. However, if the disturbance occurs during the wound-healing phase, it can cause bleeding, swelling, and infection, so that a safe alternative medicine is required, which is from an herbal plant of Kasturi bark extracts at a concentration of 12.7%. Objective: To prove the effect of the administration of Kasturi (Mangifera casturi) bark extracts at a concentration of 12.7% applied topically to the number of macrophage cells in the tooth extraction wound of Wistar rats (Rattus novergicus). Methods: This study was an Experimental Laboratories research with Post Test with Control Group Design. This study was performed on 24 Wistar rats that had been adapted ±2 weeks with a simple random sampling technique. The calculation of macrophage cells was conducted through direct observation with a light microscope and 3 visual fields. Results: The results of the study showed that Kasturi bark extracts had more effect on the number of macrophage cells than control groups. The results of One Way ANOVA showed that there is a significant relationship between each group (p<0.05). Conclusion: Kasturi bark extracts at a concentration of 12.7% can help the number of macrophage cells increase on the 3rd day and decrease on the 5th day after tooth extraction of Wistar rats. Keywords: Kasturi Bark Extract, Macrophage, Tooth Extraction.